Awareness and Utilization of e-Learning Resources by Trainee Counsellors of Counselling Education in Calabar, Nigeria - A, Okpechi, P.; P., Denwigwe, C.; N., Asuquo, P.; C., Abuo; U., Unimna, F. (International Journal of Educational Technology and Learning, 2018)
In Nigeria, electronic-learning (e-learning) resources have emerged as a modern tool for enhancing the quality of delivery and acquisition of education content. Yet, hardly has there been any meaningful research report on the application of this innovative and invaluable tool to counselling education service delivery efforts. This study, ‘awareness and utilization of e-learning resources by trainee Counsellors in counselling education in Calabar, Nigeria’ was designed to fill this literature gap. A structured questionnaire with reliability index of 0.83 titled “Awareness and Utilization of E-learning Questionnaire (AUEQ)” was used to collect data from a sample of 300 students and analyzed using t-test statistics. The results of the study indicate that while the awareness of e-learning resources by trainee Counsellors was generally high, their rating in terms of availability, currency, adequacy and quality of these resources within their schools was rather very low. The results also indicated that the extent of utilization of e-learning was also very insignificant. Furthermore, the outcomes of the study show inter-class, inter-school and inter-gender differences with regards to both awareness of availability and utilization of e-learning resources. Based on the findings, it was recommended that Universities and other higher education settings should be equipped with current, functional and adequate e-learning resources for enhanced service delivery. It was also recommended that both counsellor educators and trainees should be systematically trained in appropriate skills required for the use of e-learning facilities. It was further recommended that assurance of constant and adequate power supply should be improved upon to enhance the use of e-learning in our Universities.